Feasibility of an Electronic Patient-Reported Outcome System in People Living With HIV: Retrospective Analysis of a Mobile App-Based Pilot Study - Yusuke Yoshino; Yoshitaka Kimura; Yoshitaka Wakabayashi; Takatoshi Kitazawa (JMIR Formative Research)
Abstract BackgroundAdvances in antiretroviral therapy have transformed HIV into a manageable chronic condition, allowing people living with HIV to live longer. However, with aging, people living with HIV face increased risks of lifestyle-related diseases and unaddressed psychosocial issues, including stigma, discrimination, and mental health concerns. Patient-reported outcomes are essential tools in person-centered care and have demonstrated clinical utility in oncology and rheumatology; yet remains underutilized in infectious disease settings. Recently, the European AIDS Clinical Society has recommended electronic patient-reported outcome (ePRO) systems to support HIV care. ObjectiveThis study aimed to evaluate the feasibility and clinical utility of a smartphone-based ePRO system specifically developed for people living with HIV in Japan. MethodsA retrospective study was conducted among people living with HIV who attended the HIV outpatient clinic at Teikyo University Hospital between July and September 2022. Participants who consented to use the ePRO system installed a smartphone app and completed the HIV symptom index prior to their clinic visit. Physicians reviewed the responses during consultations; following the visits, patients completed a usability survey addressing clarity, response time, satisfaction, communication quality, and intention for future use. Medical records were reviewed to determine any new symptoms, findings, or medical actions that had not been documented in the previous two years. ResultsA total of 27 people living with HIV (median age, 46 years; 100% male) used the ePRO app, and 25 (93%) completed the postuse questionnaire. Of these, 19/25 (76%) completed the Symptom Index within 5 minutes, while one participant required more than 15 minutes. Regarding usability, 76% (n=19) reported being satisfied or very satisfied, and 76% (n=19) found the system useful in improving communication with their provider. Additionally, 76% (n=19) expressed willingness to use the system again, while 5 (20%) participants indicated interest only if improvements were made. Medical record analysis revealed that 17/27 patients (63%) had new clinical information documented, including mental health symptoms (n=7, 26%), skin problems (n=7, 26%), and new diagnoses or treatment changes in 6 (22%) cases. Over 40% (n=11) of patients reported issues such as anxiety, insomnia, dermatological symptoms, or concerns related to body image. ConclusionsThis pilot study demonstrated that a smartphone-based ePRO system for people living with HIV is feasible and well-accepted in real-world clinical practice. It facilitated early detection of psychosocial and physical issues that may otherwise be overlooked in routine care and improved patient–provider communication. These findings support the integration of ePRO systems into HIV care and underscore the need for further refinement of the app and prospective studies to assess long-term impact on patient outcomes and quality of care.